Alexithymia and perception of emotional information: A review of experimental psychological findings (2013)
Alexithymia represents a personality trait construct characterized primarily by difficulties in the capacity to identify and verbalize emotions. In the present paper, we review the existing results from psychological studies based on behavioral methods with respect to the automatic and controlled processing of external emotional information (i.e. originating outside of the body). There is evidence that alexithymia is associated with impairments in the ability to label and recognize emotional facial expression and lexical stimuli at a controlled processing level. In addition, there is preliminary evidence for a relation between alexithymia and reduced automatic attention allocation to emotional lexical stimuli. In the large majority of previous studies alexithymic characteristics have been assessed by selfreport instruments. To reach stronger conclusions about emotion perception in alexithymia future research has to complement self-descriptive with objective or direct measures of alexithymia such as standardized interview methods.